Health Goals for Perfluorinated Alkyl Substances (PFAS): A Review of Branched Isomers, the Role of Industrial Sources, and the Implications of Pfas in Biosolids on End-of-Life Disposal Methods - (:unkn) unknown (My University, 2021)
Per- and polyfluorinated alkyl substances, or PFAS, have been used for over half a century, but have become an emerging contaminant of significant concern due to their newly found widespread occurrence and recalcitrance in the environment, their tendency to bioaccumulate, and the health effects now associated with a very low level of exposure. Many gaps in knowledge remain about the fate of these chemicals in the environment and the extent of their impacts on biota. This thesis aims to fill some of the recognized gaps in knowledge: differences between linear and branched isomers of PFAS, predicting the presence of PFAS contamination in wells, and the implications of PFAS in municipal biosolids.
Keywords: biosolids; PFAS; PFOA; PFOS